Kidsspeak: A Visual Journey Through Educational Media For Young Communicators - Bidari Andaru Widhi; Panji Tanashur; Nur Alfilail (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
In a world increasingly dominated by digital media, the ability to communicate effectively is an essential skill for personal and professional success. This study explores the transformative role of visual media in fostering children’s communication abilities through the innovative KidsSpeak platform. Utilizing a qualitative descriptive approach, the research examines how KidsSpeak leverages vibrant illustrations, animated narratives, and interactive tools to enhance children’s cognitive, linguistic, and social development. The findings reveal that visual media captivates young minds, simplifies complex concepts, and supports information retention, making it an effective tool for improving comprehension. Through storytelling and role-playing, KidsSpeak fosters creativity, self-expression, and confidence, enabling children to articulate their thoughts and emotions effectively. The platform also emphasizes the development of critical communication skills through real-world simulations and engaging activities, preparing children for academic success and positive interpersonal relationships. A unique aspect of KidsSpeak is its emphasis on social advocacy, empowering children to use storytelling as a medium to address societal challenges such as environmental conservation and social justice. By providing a safe, supportive environment, KidsSpeak nurtures empathy, confidence, and a sense of agency in young communicators, equipping them to make meaningful contributions to their communities. This study highlights the potential of educational media to shape young minds and underscores the importance of integrating visual storytelling into learning experiences. The findings advocate for expanding programs like KidsSpeak to diverse cultural and linguistic contexts to further enhance their impact and inclusivity, fostering a generation of confident, creative, and socially responsible communicators.